Experimenting 'design' to reveal cultural factors - Abdul Rahman, Ahmad Rizal (Universiti Putra Malaysia Press, 2010)
New designs should support the everyday environment and should refer to existing designs that are familiar to users. These would help to motivate designers to develop culturally localised designs that allow products to be manufactured and relevant to users' current lifestyles. Despite the growing number of studies on cultural factors in marketing research, designers have not been given much opportunities to present their designing skills and thinking in conducting such research related to cultural thus leading to product improvement. This article describes a framework and results of adapting a "practice-led" research-based approach to understand cultural factors of a specific ethnic group in Malaysia whose members migrated from traditional rural life to urban industrial setting. Findings from adapting this method have been generated into a design-research guideline for designers and product planners to understand users' culturally determined needs when developing a cultural product.